The Role of Conservative Management of Modified Moderate Alvarado Score(4-7) in Acute Appendicitis - Hassan AbdulKarim , Nawshirwan; Hassan Faraj, Faruk (Diyala Journal of Medicine, 2020)
Background: Reginald Fitz described appendicitis in 1886.1From then the term appendicitis has been used. Acute appendicitis is the Commonest cause of abdominal surgical intervention with a prevalence of nearly 1 in 7 people[2].It is related to occasional mortality and high morbidity. Regarding conservative management an initial non-operative management for acute appendicitis was tried in the 1950s but was not accepted at that time[16] .Conservative management of acute appendicitis is safe and associated with reduced rate of operation ,complication and reduced costs of treatment[17-18]. Treatment include bowel rest, intravenous antibiotic with3rd generation Cephalosporine and Metronidazole .Datas show successful result in 90% of patients in whom appendicitis was confirmed by CT however 1/4 of patients may require surgical intervention within one year [19]. Objective: To assess the role of conservative management of acute appendicitis in patients with Modified Moderate Alvarado Score of (4-7). Patients and Methods: This is a prospective study conducted in Sulaymanya Teaching Hospital from December 2017 to December 2018 .A total number of 100 cases of acute appendicitis who were admitted in the emergency department with Modified Moderate Alvarado score (4-7)had been included. All the cases of the study were collected and all these patients received treatment and they divided into two groups according to the response and failure of treatment . Group A consist of ( 59%) patients in whom conservative treatment had been succeeded group B included (41%) patients in whom conservative treatment had been failed . The two groups were comparable according to age, gender and comorbidity . Inclusion crieteria include patients with Alvarado score ( 4-7). Exclusion crieteria include patients with high and low Alvarado Score , Appendicular Abscess, Appendicular mass, Fecolith, pregnant ladies, ectopic pregnancy and ovarian cyst. Results: Finally a total 100 patient were included in this study the success rate of conservative treatment of Acute Appendicitis was 59 % the failure rate was 41 %. Conclusion: in this study the result indicate that Conservative management of acute appendicitis of Modified Moderate Alvarado Score (4-7) is safeand reduces the rate of non-indicated surgery and reduces the rate of morbidity related to operation from those selected patients, and in this study the result also indicates that conservative management is successful in cases with Modified Moderate Alvarado score(4-7).